Target costing implementation and organizational capabilities: a research framework / Hussein Hamood, Normah Omar and Suzana Sulaiman - Hamood, Hussein; Omar, Normah; Sulaiman, Suzana (Faculty of Accountancy, 2013)
Target Costing (TC) has been successfully implemented to bring customers’ needs back to the products design and development stage. The best practice of TC depends aggressively on organizational capabilities (OCs) where organizational functions are combined with cross-functional teams. This paper reviews the literature carried out from 1993-2012 on TC implementation and OCs as the success factors influencing TC. The review revealed that there were two research gaps; firstly the dimension(s) used by the literature to represent OCs as success factors for TC implementation has been fairly simplistic, emphasizing on “financial” or “non-financial” variables. Secondly, the OCs dimensions have not been specifically measured. Based on the research gaps identified, a research framework is developed. The paper intend to develop a framework that link the TC principles of “Price-led”, “Customer-focused”, “Design-centered”, and “Cross-functional” with the four BSC’s perspectives of 'Financial', 'Customer', 'Internal Process', and “Learning and Growth”. The proposed framework aims to get the right balance across the crucial elements of TC including cost reduction, quality, functionality, and lead time.